STUDI FENOMENOLOGI PENERAPAN PORTOFOLIO DIGITAL SEBAGAI MEDIA PEMBELAJARAN MANDIRI - Freddy Yakob; Sanjaya Pinem; Yesa Afriansyah Norva (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Online learning encourages the creation of digital portfolios as a medium to document student work. The problem is that every digital portfolio is made to be just a media for publishing and collecting This research aims to see how portfolios are optimally constructed or not. This research uses a qualitative approach with phenomenological research methods. The data collection technique used was using in-depth interviews with a total of five participants in the study. The data analysis is carried out in four stages: bracketing, intuition, analysing, and describing. The results of this research can provide an understanding of the construction of a structure in creating a digital portfolio. In this research found a pattern that is structured according to the purposes of the portfolio so that it can be more effective and efficient in building a portofolio.